Activation of direct and indirect pathway medium spiny neurons drives distinct brain-wide responses - Lee, Hyun Joo (Neuron, 2016)
A central theory of basal ganglia function is that striatal neurons expressing the D1 and D2 dopamine receptors exert opposing brain-wide influences. However, the causal influence of each population has never been measured at the whole-brain scale. Here, we selectively stimulated D1 or D2 receptor-expressing neurons while visualizing whole-brain activity with fMRI. Excitation of either inhibitory population evoked robust positive BOLD signals within striatum, while downstream regions exhibited significantly different and generally opposing responses consistent with – though not easily predicted from – contemporary models of basal ganglia function. Importantly, positive and negative signals within the striatum, thalamus, GPi, and STN were all associated with increases and decreases in single-unit activity, respectively. These findings provide direct evidence for the opposing influence of D1 and D2 receptor-expressing striatal neurons on brain-wide circuitry and extend the interpretability of fMRI studies by defining cell type-specific contributions to the BOLD signal.